Apports de l’imagerie satellite pour le suivi de l’impact des événements cycloniques à Madagascar - Thibault Catry; Christophe Révillion; Pascal Mouquet; Gwenaëlle Pennober (EchoGéo)
This study focuses on the use of earth observation data for the monitoring of tropical cyclones and their impact in the South-western Indian Ocean. Two recent events that occurred in Madagascar are investigated: (i) Haruna, that hit the south-western coast in February 2013 and (ii) Enawo, that hit the north-eastern coast in March 2017. The results showed that satellite imagery is suitable for the quantification of hurricane-related floods over Madagascar territory. The synergetic use of optical and SAR (Synthetic Aperture Radar) sensors, with high temporal and spatial resolution allowed to : (i) carry out a near-real time monitoring of floods caused by Haruna during the crisis and a characterization of water level subsidence in post-crisis (combining SPOT 5, RADARSAT-2 and Pléiades images), (ii) a mapping of floods related to Enawo in urban areas and in rice fields in the regions of Sambava and Maroantsetra (combining Sentinel-1, Sentinel-2, and participatory mapping).